Editorial independence in an automated media system - Max van Drunen (Internet Policy Review, 2021)
The media has increasingly grown to rely on automated decision-making to produce and distribute news. This trend challenges our understanding of editorial independence by transforming the role of human editorial judgment and creating new dependencies on external software and data providers, engineers, and platforms. Recent policy initiatives such as the EU's Media Action Plan and Digital Services Act are now beginning to revisit the way law can enable the media to act independently in the context of new technological tools and actors. Fully understanding and addressing the challenges automation poses to editorial independence, however, first requires better normative insight into the functions editorial independence performs in European media policy. This article provides a normative framework of editorial independence's functions in European media policy and uses it to explore the new challenges posed by the automation of editorial decision-making.
Keywords: 300; Editorial independence; Automated decision-making; Media policy; Journalism